2020
DOI: 10.1200/jco.20.02514
|View full text |Cite
|
Sign up to set email alerts
|

Abemaciclib Combined With Endocrine Therapy for the Adjuvant Treatment of HR+, HER2−, Node-Positive, High-Risk, Early Breast Cancer (monarchE)

Abstract: PURPOSE Many patients with HR+, HER2− early breast cancer (EBC) will not experience recurrence or have distant recurrence with currently available standard therapies. However, up to 30% of patients with high-risk clinical and/or pathologic features may experience distant recurrence, many in the first few years. Superior treatment options are needed to prevent early recurrence and development of metastases for this group of patients. Abemaciclib is an oral, continuously dosed, CDK4/6 inhibitor approved for HR+,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
510
0
40

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 656 publications
(556 citation statements)
references
References 22 publications
6
510
0
40
Order By: Relevance
“…In luminal disease, recently, the addition of cycline-dependent kinase 4/6 inhibitors (CDK4/6i) abemaciclib to endocrine therapy showed promising results in the adjuvant setting for patients at a high risk of relapse leading to a potential role of these drugs in the early stage in next few years [65]. To date, no data on the safety of CDK4/6i during pregnancy are available, so currently their use is contraindicated during pregnancy.…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…In luminal disease, recently, the addition of cycline-dependent kinase 4/6 inhibitors (CDK4/6i) abemaciclib to endocrine therapy showed promising results in the adjuvant setting for patients at a high risk of relapse leading to a potential role of these drugs in the early stage in next few years [65]. To date, no data on the safety of CDK4/6i during pregnancy are available, so currently their use is contraindicated during pregnancy.…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…Last month, Johnston et al confirmed the benefit of adjuvant CDK4/6 inhibitor therapy in combination with aromatase inhibitor therapy in the MonarchE adjuvant breast cancer clinical trial 5 . Nearly all of the targeted cancer therapies approved by the Federal Drug Administration in the last many years act by inhibiting driver oncogene activity.…”
mentioning
confidence: 99%
“…Nearly all of the targeted cancer therapies approved by the Federal Drug Administration in the last many years act by inhibiting driver oncogene activity. MonarchE is the first adjuvant trial to demonstrate that targeted therapy thought primarily to act by replacing lost normal tumor suppressor gene activity—in this case Rb activity—can be effective in prolonging disease‐free survival 5 …”
mentioning
confidence: 99%
“…The trial's interim analysis was published in the Journal of Clinical Oncology 1 and also presented at the European Society for Medical Oncology Virtual Congress in September 2020. If the study's findings are confirmed in its final analysis, it will be the first time in more than 20 years that an advance has occurred in the adjuvant treatment of this form of breast cancer according to the lead author, Professor Stephen Johnston, MA, PhD, a medical oncologist with the Royal Marsden National Health Service Foundation Trust in London.…”
mentioning
confidence: 99%